Phenylephrine Affects Peripapillary Retinal Vasculature—an Optic Coherence Tomography Angiography Study - Cheng, Jingyi; Yu, Jian; Jiang, Chunhui; Sun, Xinghuai (Frontiers in Physiology, 2017)
Purpose To evaluate and compare the effect of topical mydriatic eye drops (0.5% tropicamide alone, and a 0.5% tropicamide/0.5% phenylephrine mixture) on the retinal perfusion using optic coherence tomography angiography (OCTA). Methods The perfused vessel density in the macular and peripapillary areas of both eyes was measured in eight healthy subjects using OCTA and a split-spectrum amplitude decorrelation angiography algorithm (SSADA). Various parameters, including retinal vessel density, were obtained at baseline and again 30 min after the instillation of either the tropicamide or the tropicamide/phenylephrine mixture eye drops in the right eye. Results Following instillation of the tropicamide/phenylephrine mixture eye drops, there was a significant reduction of vessel density in the peripapillary area (from 89.63 ± 4.53% to 85.00 ± 4.14%, P = 0.034), but not in the macular areas. The mean effect size in the peripapillary area was –4.63%, and was not correlated with age, sex, or baseline vessel density. There was no reduction in vessel density in the macular or peripapillary areas after instillation of 0.5% tropicamide alone, and no reduction in vessel density in the contralateral (control) eyes. Conclusion Topical phenylephrine reduced the retinal vessel density within the peripapillary area, but not within the macular area. Therefore, studies using OCTA, especially those focusing on the peripapillary area, should take into account this effect of phenylephrine on vessel density.